INTEREST LEARNING ACTIVITIES STUDENTS IN SOCIOLOGI CLASS XI IPS 4 SMAN 1 PASAMANâ THESIS SOCIOLOGY OF EDUCATION STUDIES PROGRAM SKTIP PGRI WEST SUMATERA, PADANG, 2014 - Safitri, Helda Dira; Zafri, Zafri; Erningsih, Erningsih (Pendidikan Sosiologi, 2014)
On the subject of sociology , it still looks low student interest towards learning sociology . From the observation at that time seen the low student interest in learning sociology , it can be seen from the number of students who are noisier when the teacher explains the lesson , if given the opportunity to ask only 1 and 2 students who would ask . This study aims to describe students interest in learning activities sociology . The theory used in this study is the Gestalt theory .This study used a qualitative research case study . In this study , the determination of informants conducted by purposive sampling technique , while the informants in this study is , Principals , School Waka , Sociology Teachers , and Students of class XI IPS 4 on SMA N 1 Pasaman . The data collected in this study is primary data obtained through interviews . The data analysis technique used consists of a reduction phases , data presentation / analysis of data , and drawing conclusions .The results of this study are : 1 ) Interest in learning students views of learning activities most students do not pay attention to pay attention to what is described by the teacher and this is because teachers do not use the materials in the delivery methods vary , more teachers use the lecture method so that students feel bored. 2 ) Interest in learning students views of the activities of hearing , many students are not menedengarkan teachers explanation and this is because teachers in the delivery of learning materials using only a lecture course that many students are doing other activities. 3 ) Interest in student views of reading activities , reading activities students are still considered very low , this is because students are lazy to read the learning materials. 4 ) Interest in student views of activity recorded , in the event Siwa is still much that is not noted this was due to the use of learning methods for students boring teachers , more teachers and students using lecture methods rely on guide books recommended by teachers for learning resources. 5 ) Interest of activity asks students seen , in this activity students are still many who do not want to ask, it is because the teacher only uses the lecture method so that students do not understand what is conveyed by the teacher about the learning material. 6 ) Interest in student views of activities to answer the question , in the event the student is still considered very low , this is because the students do not understand and master the learning material presented by the teacher because the teacher only lectures in front sehinnga many students who do not pay attention. 7 ) Interest in student views of activities making the task , in this activity students being categorized, it is because a lot of students who have made the task of seeing her alone .